Next-generation ELISA diagnostic assay for Chagas Disease based on the combination of short peptidic epitopes - Mucci, Juan Sebastián (2017)
Chagas Disease, caused by the protozoan Trypanosoma cruzi, is a major health and economicproblem in Latin America for which no vaccine or appropriate drugs for large-scalepublic health interventions are yet available. Accurate diagnosis is essential for the earlyidentification and follow up of vector-borne cases and to prevent transmission of the diseaseby way of blood transfusions and organ transplantation. Diagnosis is routinely performedusing serological methods, some of which require the production of parasite lysates, parasiteantigenic fractions or purified recombinant antigens. Although available serologicaltests give satisfactory results, the production of reliable reagents remains laborious andexpensive. Short peptides spanning linear B-cell epitopes have proven ideal serodiagnosticreagents in a wide range of diseases. Recently, we have conducted a large-scale screeningof T. cruzi linear B-cell epitopes using high-density peptide chips, leading to the identificationof several hundred novel sequence signatures associated to chronic Chagas Disease.Here, we performed a serological assessment of 27 selected epitopes and of their use in anovel multipeptide-based diagnostic method. A combination of 7 of these peptides werefinally evaluated in ELISA format against a panel of 199 sera samples (Chagas-positive andnegative, including sera from Leishmaniasis-positive subjects). The multipeptide formulationdisplayed a high diagnostic performance, with a sensitivity of 96.3% and a specificity of99.15%. Therefore, the use of synthetic peptides as diagnostic tools are an attractive alternativein Chagas´ disease diagnosis.